Information communications technology and economic growth in Sub-Saharan Africa: A panel data approach. (February 2019) - Haftu, Girmay Giday
Abstract: This research empirically analyzed the impact of mobile phone and the Internet on per capita income of Sub-Saharan Africa (SSA) for the period of 2006–2015 using a panel data of 40 countries. We have employed the robust two-step system GMM. Results showed that growth in mobile phone penetration has contributed significantly to the GDP per capita of the region after controlling for a number of other variables. A 10% increase in mobile phone penetration results in a 1.2% change in GDP per capita. Therefore, improving access to mobile phones will play a critical role in reducing the poverty level of the region through raising the per capita income of the population. However, the Internet has not contributed to the per capita GDP during the study period. The insignificant impact of the Internet could be due to low penetration of the technology, low ICT skill of Internet users, lack of or insufficient local content on the global network, and the relatively immature state of the technology in the region. Therefore, governments and other stakeholders should design policies that encourage expansion of the Internet. In addition to improving Internet access, policies which focus on ICT skill development and local content creation should also be designed and implemented.